Unveiling spatial differentiation of China’s inland recreational fishing: novel insights from multi-source data - Guiying Chen; Zhengyong Yang; Qilei Zhao; Bo Han; Wenhao Sha; Zhe Chen; Xinjun Chen (Reviews in Fish Biology and Fisheries, 2026)

Correction to: Spil mediated sEH overexpression contributes to the senescence of alveolar epithelial cells during pulmonary fibrosis in mice - Chen-Yu Zhang; Wen-Jing Zhong; Jin-Tong Yang; Yan-Ling Qiu; Han-Xi Sha; An-Jun Ou; Yu-Biao Liu; Xiao-Ting Huang; Yong Zhou; Jia-Xi Duan; Cha-Xiang Guan (Journal of Molecular Medicine, 2026)

Spil-mediated sEH overexpression contributes to the senescence of alveolar epithelial cells during pulmonary fibrosis in mice - Chen-Yu Zhang; Wen-Jing Zhong; Jin-Tong Yang; Yan-Ling Qiu; Han-Xi Sha; An-Jun Ou; Yu-Biao Liu; Xiao-Ting Huang; Yong Zhou; Jia-Xi Duan; Cha-Xiang Guan (Journal of Molecular Medicine, 2026)

Improving multi-view video fusion and model generalization in pig behavior monitoring with teacher–student semi-supervised learning - Shuo Wan; Junkai Li; Feiyue Xue; Tao Han; Ying Sha; Li Qin (Computers and Electronics in Agriculture, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Genomic and biosynthetic landscape of high-temperature Daqu microbiome - Mingyue Cheng; Xing Qin; Ying Han; Fanggen Tan; Menglin She; Xue Zhu; Lin Yuan; Mengjing Teng; Xiyang Ou; Sha Luo; Ping Xiang; Liangqiang Chen; et al. (Bioresource Technology, 2026)

Fermentation optimization and characterization of extracellular protein-associated antifungal components from Bacillus velezensis SY01 against Cytospora pyri - Shuaishuai Sha; Lingkai Xu; Canpeng Fu; Qiuyan Han; Jiaqi Ding; Beibei Feng; Yan Zhang; Sabinur Nurmemet; Pan Xie (Physiological and Molecular Plant Pathology, 2026)

Abnormal spring climate and greener amplify impacts on ecosystem productivity and evapotranspiration under extreme summer drought - Shanshan Yang; Huadong Guo; Qi Liu; Jiaqi Han; Jingwen Wang; Yun Bai; Sha Zhang; Ayalkibet M. Seka; Jiahua Zhang (Environmental Impact Assessment Review, 2026)

Global Disparities in the Recreational Fishery Economy: A Systematic Review - Wenhao Sha; Guiying Chen; Bo Han; Xinjun Chen; Qilei Zhao (Fishes, 2026)
Recreational fisheries contribute significantly to global economies through tourism, employment, and ecosystem service valorization. However, a systematic understanding of their economic magnitude and regional disparities remains fragmented. This study conducts a systematic review of 112 peer-reviewed articles published between 1991 and 2024, synthesizing the economic evidence across three key domains: consumer behavior, resource management, and ecological interactions. Consistent with previous research, our systematic synthesis documents a pronounced imbalance in the existing evidence base: studies from high-income countries more frequently report established management frameworks (e.g., bag limits, catch-per-unit-effort monitoring) and robust economic valuation mechanisms (e.g., Willingness to Pay estimation), whereas low- and middle-income countries face significant barriers in infrastructure and resource quantification. We identify that non-market valuation methods, particularly the travel cost method and consumer surplus analysis, are critical for internalizing the environmental value of fisheries. Furthermore, while ecological restoration demonstrates clear positive feedback loops for local economies, the sector exhibits high vulnerability to external shocks, such as the COVID-19 pandemic. This review highlights the urgent need to bridge the data gap in developing regions and suggests that transferring successful adaptive management models from developed nations is essential for achieving equitable and sustainable growth in the global recreational fishery economy.

B-MARCO: a blockchain-driven multi-national auction and resource optimization framework for cross-border logistics and trade - Mei Sha; Shuang Li; Tao Zhang; Han Liu; Jianli Shen; Xiaohu Huang; Jiahua Hu (Frontiers in Marine Science, 2026)
Cross-border maritime logistics requires coordination among carriers, ports, customs authorities, and financial institutions, yet existing workflows are often constrained by fragmented regulatory data systems, inefficient dynamic capacity matching, and slow batch-based clearing. This paper proposes B-MARCO, a blockchain-driven multi-national auction and resource optimization framework for cross-border maritime logistics. B-MARCO integrates permissioned consortium coordination, rolling auction-based market clearing, a hybrid GA-GSA dispatching engine, and privacy-preserving access-control and compliance-verification components. The evaluation uses a semi-synthetic discrete-event simulation with a 7-day horizon, hourly decision intervals, 30 random seeds, and shared order streams across all configurations. Under a 5,000-orders/day workload, B-MARCO achieves a 91.80% transaction success rate and 21.53 h average end-to-end latency, compared with 60.09% and 36.66 h for the 24-hour batch-clearing baseline. Relative to a centralized rolling-matching baseline, it reduces average latency by 13.60%. The ablation results show that rolling auction clearing reduces latency, while smart-contract-based settlement-delay reduction is a major contributor to improved success and deadline performance. These findings support the value of combining rolling market clearing with spatial-temporal dispatch optimization in simulated cross-border maritime logistics, while the blockchain and cryptographic modules define the broader coordination, auditability, and data-governance architecture.

Functional antagonism and underlying regulatory pathways of haptoglobin splicing isoforms in the immune response of half-smooth tongue sole (Cynoglossus semilaevis) - Suxu Tan; Yixiao Hu; Wenwen Wang; Sen Han; Yu Bai; Yishuai Li; Kunpeng Shi; Shaoqing Zang; Yiming Hu; Zhenxia Sha (Fish & Shellfish Immunology, 2026)

Fibrillation of solid-solid phase change polyethylene glycol fibers assisted by cellulose nanofibers for personal thermal management - Jiaqian Xu; Lu Jia; Longcan Guo; Zhiheng Sha; Suqin Zhou; Huatao Han; Chaoran Ye; Hua Wang (Chemical Engineering Journal, 2026)

Molecular phylogeny and fossil records reveal the origin and evolutionary history of deep-sea Ophiuroidea - Han Yan; Zhongli Sha; Shao’e Sun (Frontiers in Marine Science, 2026)
Introduction The evolutionary history and biogeographic assembly of deep-sea Ophiuroidea remain incompletely understood. This study aimed to clarify the origin, spatial evolution, and long-term assembly of deep-sea ophiuroid diversity through an integrative framework. Methods We integrated multiple lines of evidence, including fossil paleogeography, taphonomic-control analyses, global biogeographic regionalization, directional dispersal asymmetry, time-calibrated molecular phylogenetic analysis, quantitative assessment of species diversification rates, and ancestral-area reconstruction. Results Fossil paleogeographic reconstructions reveal that early ophiuroid occurrences were mainly associated with shallow continental margins at low to middle paleolatitudes, followed by broader spatial expansion during the Paleozoic and a pronounced western Tethyan signal during key Mesozoic intervals. Taphonomic-control analyses show that this western Tethyan concentration remained evident after accounting for preservation opportunity, supporting the importance of this region in the historical distribution of Ophiuroidea. Analyses of extant deep-sea Ophiuroidea show that modern diversity is concentrated mainly in the Indo-Pacific, southwestern Pacific region, and the Gulf of Mexico tropical western Atlantic. Directional dispersal analyses further indicate compositional asymmetry among regions, with a strong western southern Pacific influence at the whole deep-sea scale. Depth-stratified regionalization reveals marked faunal differentiation in the mid-bathyal zone, followed by broader cross-basin connectivity in the lower bathyal and abyssal zones. Molecular dating suggests that deep-sea-associated ophiuroid lineages began to diverge in the late Paleozoic, whereas ancestral-area reconstruction highlights the importance of the Indo-Pacific region in the later biogeographic history of the sampled taxa. Diversification analyses indicate a non-constant evolutionary tempo, with temporal signals broadly consistent with repeated environmental restructuring and post-extinction ecological recovery. Conclusion Overall, these results suggest that deep-sea ophiuroid diversity was assembled through a multi-stage and multi-regional process involving ancient Tethyan historical signals, later Indo-Pacific and Pacific-centered accumulation, depth-dependent connectivity, and recurrent ecological reorganization through geological time.

MPCSD-Net: A multi-scale physically constrained self-distillation method for super-resolution reconstruction - Hongjie Sha; Zhen Han (Computers & Geosciences, 2026)

Bidirectional interfacial polymerization-architected nanoporous graphene-polyamide nanofilms for efficient antibiotic separation - Yumin Sun; Yongbo Yang; Sha Liang; Yihang Zhang; Qinglin Huang; Xutong Han; Changfa Xiao; Wei Li; Kaikai Chen; Xianhui Li; Yang Yang; Hailiang Liu (Chemical Engineering Journal, 2026)

Seasonal dependence of oxidative toxicity of atmospheric fine particulate matter: A case study of Xi’an, a megacity in Northwest China - Bo Wang; Qingcai Chen; Jiale Ding; Yuemei Han; Tong Sha; Qingwen Wang; Xin Zhu; Xin Zhang; Lijuan Li; Yang Li (Journal of Hazardous Materials, 2026)

Promoting the formation of soybean protein isolate amyloid fibrils and self-assembled hydrogels with antibacterial activity through plasma-activated water induction - Liming Tan; Han Hu; Lijun Yin; Xin Jia; Kun Sha; Haijie Liu (Food Hydrocolloids, 2026)

Biogas upgrading via microbial electrolysis cell-integrated anaerobic digestion: A critical review of stabilization strategies towards practical application - Sha Tan; Lei Li; Shuang Liu; Linpei Han; Chaoran Duan; Yongli Liu; Xiaoming Wang (Journal of Environmental Management, 2026)

Smart "artificial aerogel wool": Multi-responsive polyacrylonitrile aerogel fiber for personal healthcare and thermal management textiles - Xiangyuan Yan; Qiankun Sha; Jin Wang; Changhui Ma; Guang Peng Luo; Xingxiang Zhang; Jinlei Miao; Na Han (Chemical Engineering Journal, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Comparative study of the effects of pristine and aged PBAT microplastics on soil microbial community composition and nitrogen transformation - Aoyu Zhou; Sha Chang; Yuxiao Jiang; Jiru Li; Fengxiao Zhu; Han Meng; Jian Xu; Shiyin Li; Huan He (Journal of Soils and Sediments, 2026)

Modulation of the nanoscale chimney effect in metal–organic frameworks enables efficient guest diffusion and separation - Sha-Sha Meng; Hanxi Guan; Han Yang; Hai-Yue Wei; Mo-Han Gu; Jian Zhang; Ming Xu; Lina Wu; Zhi-Yuan Gu (Science Bulletin, 2026)

Sustainable lightweight composite nanofibers: efficient control of electromagnetic pollution - Miao Li; Mengxiang Liu; Zihan Kong; Qiong Wu; Yuqi Liu; Sha Han; Tao Zhang; Xiaoxiao Huang (Journal of Cleaner Production, 2026)

Algae penetration and taste and odor compounds production in drinking water treatment plants: seasonal variations and risk assessment - Ya Cheng; Caiyun Ma; Gang Wen; Chaoyang Zheng; Wenle Tian; Kailin Sha; Xinru Han; Tinglin Huang (Journal of Environmental Sciences, 2026)

Progressive Failure Characteristics and Damage Evolution of Anisotropic Rocks with Oriented Arrangement of Minerals Under Triaxial Cyclic Loading and Unloading - Dahai Wang; Changqing Liu; Han Bao; Hengxing Lan; Peng Sha; Bo Li; Shijie Liu; Changgen Yan (Rock Mechanics and Rock Engineering, 2026)

Revealing the mechanism of nitrogen migration during the pyrolysis of 3-amine caprolactam: Integrated experimental and DFT simulation studies - Zhenqing Han; Jun Shen; Yun Guo; Shengxiang Deng; Sha Wang; Haiyong Peng; Chen Zhang (Fuel, 2026)

Fracture Characteristics and Quantitative Analysis of Anisotropic Rock with Direction-Arranged Minerals Subjected to Triaxial Cyclic Loading: A Case of Biotite Quartz Schist - Han Bao; Yankai Wang; Changqing Liu; Qun Qi; Hengxing Lan; Shengwen Qi; Bo Li; Peng Sha; Hongtao Lv (Rock Mechanics and Rock Engineering, 2025)

Blocking triggering receptors expressed on myeloid cell-1 alleviates alveolar epithelial cell senescence by inhibiting oxidative stress in pulmonary fibrosis - Wen-Jing Zhong; Jian-Bing Xiong; Chen-Yu Zhang; Ling Jin; Nan-Shi-Yu Yang; Han-Xi Sha; Yu-Biao Liu; Jia-Xi Duan; Cha-Xiang Guan; Yong Zhou; Feng Su (Histochemistry and Cell Biology, 2025)

Multi-criteria carbon emission allowance allocation for liner shipping companies in China: An integrated approach based on composite indicators and zero-sum gains DEA - Mo Zhu; Yuquan Du; Mei Sha; Yiwen Jiang; Zhongdai Wu; Bing Han (Ocean & Coastal Management, 2025)

Novel alkali-resistant nitrogen and phosphorus removal strain I4: Performance evaluation and molecular mechanism - Xiaoxuan Fan; Jiayi Zhou; Qionghua Chen; Yuwei Feng; Ruirui Han; Guangfeng Chen; Sha Yue; Yonghao Ma; Hu Shu (Bioresource Technology, 2025)

Unveiling dynamics of microbial communities, species interactions, and ecological assembly during low-temperature-induced sludge bulking in full-scale wastewater treatment systems - Han-Jun Sun; Xian Zhao; Jie Ding; Yu-Qian Wang; Wen-Shuo Wang; Zhi-Hua Feng; Sha Zhao; Liang Wang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2025)

Salvianolic Acid B and Ginsenoside Rg1 Combination Attenuates Cerebral Edema Accompanying Glymphatic Modulation - Lingxiao Zhang; Yanan Shao; Zhao Fang; Siqi Chen; Yixuan Wang; Han Sha; Yuhan Zhang; Linlin Wang; Yi Jin; Hao Chen; Baohong Jiang (Neuroscience Bulletin, 2025)

Precise Magnetic Stimulation of the Paraventricular Nucleus Improves Sociability in a Mouse Model of ASD - Sha Liu; Quyang Yang; Pengfei Zhu; Xuan Liu; Qingbo Lu; Jie Yang; Jingyao Gao; Hongbin Han; Zhijun Zhang; Ning Gu; Tao Tan; Jianfei Sun (Neuroscience Bulletin, 2025)
Magnetic stimulation has made significant strides in the treatment of psychiatric disorders. Nonetheless, current magnetic stimulation techniques lack the precision to accurately modulate specific nuclei and cannot realize deep brain magnetic stimulation. To address this, we utilized superparamagnetic iron oxide nanoparticles as mediators to achieve precise targeting and penetration. We investigated the effects of magnetic fields with varying frequencies on neuronal activity and compared the activation effects on neurons using a 10-Hz precise magneto-stimulation system (pMSS) with repetitive transcranial magnetic stimulation in mice. Oxytocin levels, dendritic morphology and density, and mouse behavior were measured before and after pMSS intervention. Our findings suggest that pMSS can activate oxytocinergic neurons, leading to upregulation of oxytocin secretion and neurite outgrowth. As a result, sociability was rapidly improved after a one-week pMSS treatment regimen. These results demonstrate a promising magneto-stimulation method for regulating neuronal activity in deep brain nuclei and provide a promising therapeutic approach for autism spectrum disorder.

Recessive variants in TWNK cause syndromic and non-syndromic post-synaptic auditory neuropathy through MtDNA replication defects - Xue Gao; Ying Ma; Wei-Qian Wang; Guo-Jian Wang; Kun Yang; Jin-Cao Xu; Sha-Sha Huang; Xiang Wang; Li-Min Hu; Xi Wang; Qiu-Quan Wang; Zhen-Dong Wang; et al. (Human Genetics, 2025)

What does the dairy farming bring to the desertified soil? A case study - Zixi Han; Jianfei Zeng; Xu Zhao; Yanyan Dong; Yongsong Mu; Sha Wei; Yong Hou; Ziyu Han (Agricultural Systems, 2025)

Identification of an adaptor protein 2σ gene for OsTGW12 to determine grain weight and potentiate quality breeding in rice - Xiaoqiong Li; Huangai Li; Ke Xie; Jinling Han; Kaiqiang Liu; Ying Chen; Jingang Qi; Hongpei Jin; Hanhua Tong; Aihua Sha; Sibin Guo (Theoretical and Applied Genetics, 2025)

Improving the edible quality of deacetylated konjac glucomannan gel: Synergistic ethanol immersion and low-temperature pretreatment - Sha Li; Wenfeng Han; Jing Li; Bin Li (Innovative Food Science & Emerging Technologies, 2025)

SHP-1 negatively regulates LPS-induced M1 polarization, phagocytic activity, inflammation and oxidative stress in primary macrophages of Chinese tongue sole (Cynoglossus semilaevis) - Ningning Wang; Suxu Tan; Hui Liu; Yanzhao Nie; Muyuan Wang; Hongning Liu; Sen Han; Zhendong Wu; Jie Ma; Zhenxia Sha (Fish & Shellfish Immunology, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

SHP-1 interacts with NFκB1 to inhibit its phosphorylation and nuclear translocation to exert its anti-bacterial function - Ningning Wang; Suxu Tan; Muyuan Wang; Hongning Liu; Sen Han; Zhendong Wu; Jie Ma; Songlin Chen; Zhenxia Sha (Aquaculture, 2025)

Poly(vinylidene fluoride)-based Janus separators with an ultrathin conductive layer for suppressing lithium dendrite growth - Ruiqi Che; Sha Cheng; Cheng Huang; Ming Liu; Zhongao Chen; Jin Han; Wen Chen; Pengchao Zhang (Chemical Engineering Journal, 2025)

Increase of ATP synthesis and amino acids absorption contributes to cold adaptation in Antarctic bacterium Poseidonibacter antarcticus SM1702T - Wen-Yue Xu; Sha-Sha Liu; Xiao-Han Guo; Peng Wang; Chun-Yang Li; Li Liao; Qi-Long Qin (Extremophiles, 2025)

Sulfur dioxide increases testosterone biosynthesis by activating ERK1/2 pathway and disrupting autophagy in Leydig cells - Xiang Li; Yan Shi; Sha Liu; Zhiyuan Feng; Haoran Xiao; Rui Li; Zirou Li; Xinyue Zhang; Yongli Han; Jundong Wang; Chen Liang; Jian Bai; et al. (Journal of Hazardous Materials, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Lipidomics analysis of adipose depots at differently aged Sunit sheep - Lu Chen; Xige He; Yunfei Han; Yajuan Huang; Jin Li; Jin Li; Xueting Yu; Xueyan Yun; Jindi Wu; Rina Sha; Tungalag Dong; Gerelt Borjigin (Food Chemistry, 2025)

Forest thinning effects on soil carbon stocks and dynamics: Perspective of soil organic carbon sequestration rates - Qing Qu; Hongwei Xu; Lin Xu; Chengming You; Bo Tan; Han Li; Li Zhang; Lixia Wang; Sining Liu; Zhenfeng Xu; Sha Xue; Minggang Wang (CATENA, 2025)

The ratio of transpiration to evapotranspiration dominates ecosystem water use efficiency response to drought - Shanshan Yang; Jiahua Zhang; Jiaqi Han; Yun Bai; Lan Xun; Sha Zhang; Dan Cao; Jingwen Wang (Agricultural and Forest Meteorology, 2025)

In-depth understanding the pyrolysis behavior of arginine: Combined experiments, ReaxFF molecular dynamics and DFT calculation study - Ziqi Wang; Jun Shen; Xuesong Liu; Sha Wang; Shengxiang Deng; Zhenqing Han; Hai Zhang; Yun Guo (Fuel, 2025)

m6A methylation dynamically participates in the immune response against Vibrio anguillarum in half-smooth tongue sole (Cynoglossus semilaevis) - Suxu Tan; Wenwen Wang; Sen Han; Ruixue Zhang; Kunpeng Shi; Shaoqing Zang; Zhendong Wu; Zhenxia Sha (Fish & Shellfish Immunology, 2025)

A framework of ecological security patterns in arid and semi-arid regions considering differences socioeconomic scenarios in ecological risk: Case of Loess Plateau, China - Jin Guo; Pengfei Feng; Han Xue; Sha Xue; Liangxin Fan (Journal of Environmental Management, 2025)

Reseeding increased plant biomass production and soil fertility, but not plant species diversity in degraded grasslands in China - Hasbagan Ganjurjav; Mingjie Li; Ling Han; Yubao Sha; Zheng Li; Xuyang Han; Guoxu Ji; Rihan Wu; Yandan Ma; Guozheng Hu; Elise Gornish; Qingzhu Gao (Journal of Environmental Management, 2024)

Short-term usage of proton pump inhibitors during admission was associated with increased risk of rehospitalization in critically ill patients with myocardial infarction: a cohort study - Jia-De Zhu; Li-Juan Yang; Jian-Nan Zhao; Ping Wang; Yi-Hua Li; Xue-Sha Zhang; Jian-Mei Pan; Meng-Han Jiang; Hai-Ying Yang; Sun-Jun Yin; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

The survival, gene expression, and DNA methylation of Paralichthys olivaceus impacted by the decay of green tide and bacterial infection in both laboratory and field simulation experiments - Jie Ma; Kunpeng Shi; Weijun Zhang; Sen Han; Zhendong Wu; Muyuan Wang; Haibo Zhang; Jiacheng Sun; Ningning Wang; Mengyang Chang; Xiaoyong Shi; Suxu Tan; et al. (Science of The Total Environment, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

Manipulated C5aR1 over/down-expression associates with IL-6 expression during bacterial inflammation in half-smooth tongue sole (Cynoglossus semilaevis) - Zhendong Wu; Shaoqing Zang; Wenwen Wang; Suxu Tan; Qian Xu; Xuejie Chen; Sen Han; Jie Ma; Kunpeng Shi; Ningning Wang; Jiayu Cheng; Zhenxia Sha (Fish & Shellfish Immunology, 2024)

Wave, flow, and suspended sediment dynamics under strong winds on a tidal beach - Lingpeng Meng; Junbiao Tu; Xiaodong Wu; Sha Lou; Jun Cheng; Sergey Chalov; Xiangju Han; Daidu Fan (Estuarine, Coastal and Shelf Science, 2024)

Conformational transformation of activator strand directly regulates CRISPR/Cas12a system activity for live cell sensing of multiple biomolecules - Qing-Nan Li; Dong-Xia Wang; Zhi-Qi Dai; Shun-Li Wu; Gui-Mei Han; Sha Lu; Li-Na Zhu; Hong-Xin Jiang; De-Ming Kong (Chemical Engineering Journal, 2024)

ETE-SRSP: An Enhanced Optimization of Tramp Ship Routing and Scheduling - Xiaohu Huang; Yuhan Liu; Mei Sha; Bing Han; Dezhi Han; Han Liu (Journal of Marine Science and Engineering, 2024)
In the contemporary tramp shipping industry, route optimization and scheduling are directly linked to enhancements in operations, economics, and the environment, making them key factors for the effective management of maritime transportation. To enhance effective ship-to-cargo matching and the refinement of maritime transportation itineraries, this paper introduces a time efficiency and carbon dioxide emission multi-objective optimization algorithm named ETE-SRSP (efficiency–time–emission multi-optimization algorithm). ETE-SRSP incorporates several factors, including the initial positions of ships, time windows for loading and unloading operations, and varying sailing speeds. Within the ETE-SRSP framework, pioneering an approach that integrates ballast and laden sailing velocities as decisional parameters, it employs a multi-objective optimization technique to investigate the intricate interplay between temporal efficiency and carbon dioxide emissions. Additionally, the model’s proficiency in mitigating emissions and managing costs is clearly demonstrated through the optimization of these objectives, thereby offering a robust framework for decision support. The experimental results show that the optimal sailing speeds derived from the ETE-SRSP, under typical time-weight scenarios, can achieve an optimal balance between emission reduction and cost control. In summary, this study underscores the optimization strategy’s potential to effectively address the maritime sector’s need for economic growth and ecological conservation, showcasing its practical value in the industry.

Poly(vinylidene fluoride)-based composite membranes with continuous metal–organic framework layer for high-performance separators of lithium-ion batteries - Mengying Li; Sha Cheng; Jisong Zhang; Cheng Huang; Jiapei Gu; Jin Han; Xu Xu; Xiao Chen; Pengchao Zhang; Ya You (Chemical Engineering Journal, 2024)

Gastrodin Regulates PI3K/AKT-Sirt3 Signaling Pathway and Proinflammatory Mediators in Activated Microglia - Han-Jun Zuo; Peng-Xiang Wang; Xue-Qi Ren; Hao-Long Shi; Jin-Sha Shi; Tao Guo; Cheng Wan; Juan-Juan Li (Molecular Neurobiology, 2024)

Growth differentiation factor 9 regulates the expression of estrogen receptors via Smad2/3 signaling in goat cumulus cells - Yaju Tang; Sihai Lu; Juncai Wei; Rui Xu; Hui Zhang; Qiang Wei; Bin Han; Yan Gao; Xiaoe Zhao; Sha Peng; Menghao Pan; Baohua Ma (Theriogenology, 2024)

PPS/TA-PEI/β-FeOOH membranes with powerful photo-Fenton self-cleaning capability for efficient oil–water emulsion separation - Shiwei Tian; Yaqi Zhang; Qiankun Sha; Xingxiang Zhang; Tian Yang; Xuhuan Yan; Na Han (Chemical Engineering Journal, 2024)

Preconditioning exercise reduces brain damage of ischemic stroke in rats via PI3K–AKT pathway by bioinformatic analysis - Kai Li; Zhen-Kun Gao; Yi-Sha Guo; Xin-Ya Shen; Yu Han; Mei Yuan; Xia Bi (Experimental Brain Research, 2024)

Analysis of alternative splicing provides insights into its vital roles in immune responses of half-smooth tongue sole (Cynoglossus semilaevis) against Vibrio anguillarum - Sen Han; Suxu Tan; Hongning Liu; Ningning Wang; Xinbao Liu; Zhujun Li; Zhendong Wu; Jie Ma; Wenwen Wang; Kunpeng Shi; Zhenxia Sha (Aquaculture, 2024)

Novel insights into deep-sea hydrothermal vent and cold seep adaptation inferred from comparative transcriptome analysis of a munidopsid squat lobster distributed in both environments - Jiao Cheng; Han Yan; Min Hui; Zhongli Sha (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Tetracycline removal from soil by phosphate-modified biochar: Performance and bacterial community evolution - Wei Han; Meng Zhang; Ying Zhao; Weichang Chen; Huixin Sha; Lei Wang; Yiran Diao; Yuanji Tan; Ying Zhang (Science of The Total Environment, 2024)

Middle to late Eocene charophytes from the Gaize Basin in central Tibet - Yi Xing; Sha Li; Bowen Song; Gaolei Jiang; Yi Wei; Fang Han; Kexin Zhang (Review of Palaeobotany and Palynology, 2024)

3D network of zinc powder woven into fibre filaments for dendrite-free zinc battery anodes - Lin Sha; Bin-Bin Sui; Peng-Fei Wang; Zhe Gong; Yu-Hang Zhang; Yu-Han Wu; Li-Na Zhao; Jun-Jie Tang; Fa-Nian Shi (Chemical Engineering Journal, 2024)

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

Selaginellin derivatives from Selaginella tamariscina and evaluation for anti-breast cancer activity - Jing Wen; Dong-Mei Sha; Xiao-Yong He; Yu-Han Tian; Shuai-Cong Ni; Bin He; Yuan Liu; Xin-Jia Yan (Phytochemistry, 2024)

Effects of miR-722 on gene expression and alternative splicing in the liver of half-smooth tongue sole after infection with Vibrio anguillarum - Hongning Liu; Suxu Tan; Sen Han; Xinbao Liu; Zhujun Li; Ningning Wang; Zhendong Wu; Jie Ma; Kunpeng Shi; Wenwen Wang; Zhenxia Sha (Fish & Shellfish Immunology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Covalent organic framework functionalized smart membranes with under-liquid dual superlyophobicity for efficient separation of oil/water emulsions - Yaqi Zhang; Shiwei Tian; Qiankun Sha; Jinjie Lv; Na Han; Xingxiang Zhang (Science of The Total Environment, 2023)

Proteomic advance of ischemic stroke: preclinical, clinical, and intervention - Tian Zhao; Jingjing Zeng; Ruijie Zhang; Liyuan Pu; Han Wang; Lifang Pan; Yannan Jiang; Xiaoyu Dai; Yuyi Sha; Liyuan Han (Metabolic Brain Disease, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Co3S4/MoS2 heterostructure on N-doped porous carbon for boosted peroxidase-like activity and sensitive biosensing - Mingqi Xu; Wenwen Wang; Hong Han; Yupu Wei; Jingquan Sha; Guodong Liu (Chemical Engineering Journal, 2023)

Hierarchical wood cells impose well-textured carbon nanotubes with cobalt single atoms: Bioinspired construction and application in zinc–air battery - Yangyang Chen; Ying Wu; Lei Li; Yu Liao; Sha Luo; Han Xu; Yiqiang Wu; Yan Qing (Chemical Engineering Journal, 2023)

Responses of bacterial community composition and diversity to multi-level nitrogen addition at different periods of growing season driven by conditional rare taxa in an alpine meadow - Yilun Hu; Hasbagan Ganjurjav; Guozheng Hu; Guoxu Ji; Lin Han; Yubao Sha; Yan Liang; Qingzhu Gao (Biology and Fertility of Soils, 2023)

Mowing increased plant diversity but not soil microbial biomass under N-enriched environment in a temperate grassland - Qiushi Ning; Liangchao Jiang; Guoxiang Niu; Qiang Yu; Jushan Liu; Ruzhen Wang; Sha Liao; Jianhui Huang; Xingguo Han; Junjie Yang (Plant and Soil, 2023)

C5a drives the inflammatory response with bacterial dose effect by binding to C5aR1 in zebrafish infected with Aeromonas hydrophila - Xinbao Liu; Wenwen Wang; Suxu Tan; Hongning Liu; Zhujun Li; Ningning Wang; Jie Ma; Sen Han; Zhendong Wu; Kunpeng Shi; Zhenxia Sha (Fish & Shellfish Immunology, 2023)

Chromosome-specific painting in Thinopyrum species using bulked oligonucleotides - Chen Chen; Yangshuo Han; He Xiao; Bingcan Zou; Dandan Wu; Lina Sha; Cairong Yang; Songqing Liu; Yiran Cheng; Yi Wang; Houyang Kang; Xing Fan; et al. (Theoretical and Applied Genetics, 2023)

Solvent-free quasi-solid polymer electrolyte with a high dielectric constant for stable lithium metal anodes - Xuechun Lou; Jun Zhong; Danpeng Cheng; Qigao Han; Fuhe Wang; Shuaijing Ji; Wuxin Sha; Fengqian Wang; Jie Tian; Weixin Zhang; Shun Tang; Yuan-Cheng Cao; et al. (Chemical Engineering Journal, 2023)

The driving force of biomass value-addition: Selective catalytic depolymerization of lignin to high-value chemicals - Quyang Tian; Piao Xu; Danlian Huang; Han Wang; Ziwei Wang; Hong Qin; Yangzhuo He; Ruijin Li; Lingshi Yin; Sha Chen; Yin Zhao (Journal of Environmental Chemical Engineering, 2023)

Polycrystalline ZSM-5@Beta core–shell composites fabricated by a seed-directed approach: A catalyst to boosting light olefin production by ordered hierarchical cracking - Lei Han; Ruoyu Wang; Peng Wang; Yuchen Sha; Aiguo Zheng; Qiuqiao Jiang; Mudi Xin; Haitao Song; Wei Lin (Fuel, 2023)

Adaptation to high latitudes through a novel allele of Hd3a strongly promoting heading date in rice - Zhongmin Han; Xiangliang Lei; Hanjing Sha; Jia liu; Chuanzhong Zhang; Jingguo Wang; Hongliang Zheng; Detang Zou; Jun Fang (Theoretical and Applied Genetics, 2023)

Effect Analysis of Different Environmental Disinfection Methods on Reducing Contamination of Surfaces by the Omicron BA.2.2 Variant of SARS-CoV-2 and the Characteristics of Fomite Contamination in the Fever Clinic in the Out-Broken of Shanghai - Lei Yang; Wenfang Dong; Xiaoyu Shen; Feng Han; Chenxi Liu; Yirou Wang; Xuemei Xu; Yufen Wu; Sha Zhou; Qing Cao (Food and Environmental Virology, 2023)
This study aimed to investigate the effect of different environmental disinfection methods on reducing contaminated surfaces (CSs) by the Omicron BA.2.2 variant of SARS-CoV-2 in the fever clinic between March 20 and May 30, 2022, and to analyze the influences and related factors of CSs. This study includes survey data from 389 positive patients (SPPs) and 204 CSs in the fever clinic, including the CS type, disinfection method, length of time spent in the clinic, cycle threshold (CT) value, name, age, weight, mask type, mask-wearing compliance, hand-mouth touch frequency and sex. Associations between study variables and specified outcomes were explored using univariate regression analyses. Mask-wearing compliance had a significant negative correlation with CSs ( r = − 0.446, P = 0.037). Among the 389 SPPs, 22 SPPs (CRP, 5.66%) caused CSs in the separate isolation room. A total of 219 SPPs (56.30%) were male. The mean age of SPPs was 4.34 ± 3.92 years old, and the mean CT value was 12.44 ± 5.11. In total, 9952 samples with exposure history were taken, including 204 (2.05%) CSs. Among the CSs, the positive rate of flat surfaces was the highest in public areas (2.52%) and separate isolation rooms (4.75%). Disinfection methods of ultraviolet radiation + chemical irradiation significantly reduced the CSs in both the public area (0% vs. 4.56%) and the separate isolation room (0.76% vs. 2.64%) compared with the chemical method alone ( P < 0.05). Compared with ordinary SPPs, CRPs were older (6.04 year vs. 4.23 year), and the male proportion was higher (72.73% vs. 55.31%). In particular, it was found that SPPs contaminated their surroundings and therefore imposed risks on other people. Environmental disinfection with ultraviolet radiation + chemical treatment should be emphasized. The findings may be useful to guide infection control practices for the Omicron BA.2.2 variant of SARS-CoV-2.

Co-pyrolysis technology for enhancing the functionality of sewage sludge biochar and immobilizing heavy metals - Zeyu Fan; Xian Zhou; Ziling Peng; Sha Wan; Zhuo Fan Gao; Shanshan Deng; Luling Tong; Wei Han; Xia Chen (Chemosphere, 2023)

Contribution of the TGFβ signaling pathway to pigmentation in sea cucumber (Apostichopus japonicus) - Linlin Yao; Bin Zhao; Qi Wang; Xuyang Jiang; Sha Han; Wei Hu; Chenglin Li (Frontiers in Marine Science, 2023)
Pigmentation mediated by the transforming growth factor β (TGFβ) signaling pathway is a key trait for understanding environmental adaptability and species stability. In this study, TGFβ signaling pathway members and their expression patterns in different color morphs of the sea cucumber Apostichopus japonicus were evaluated. Using a bioinformatics approach, 22 protein sequences of TGFβ signaling pathway members in A. japonicus were classified, including 14 that were identified for the first time in the species, including 7 ligands, 6 receptors, and 1 R-Smad. We further evaluated mRNA expression data for different color morphs and pigmentation periods. These results support the hypothesis that both subfamilies of the TGFβ superfamily, i.e., the TGFβ/activin/Nodal and BMP/GDF/AMH subfamilies, are involved in the regulation of pigmentation in A. japonicus . The former subfamily was complete and contributes to the different color morphs. The BMP/GDF/AMH subfamily was incomplete. BMP2/4-induced differentiation of white adipocytes was regulated by the BMP2/4–ACVR2A–Smad1 signaling pathway. These findings provide insight into the TGFβ family in early chordate evolution as well as the molecular basis of color variation in an economically valuable species.

Study on sex-linked region and sex determination candidate gene using a high-quality genome assembly in yellow drum - Sha Sun; Chaowei Song; Fang Han; Qiwei He; Jieping Liu; Sen Zhang; Wei Han; Kun Ye; Zhaofang Han; Zhiyong Wang; Wanbo Li (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Network pharmacological investigation into the mechanism of Kaixinsan powder for the treatment of depression - Li-Jing Du; Xin-Ning Zhang; Sha-Sha Li; Yuan-Fang Sun; Hui-Zi Jin; Shi-Kai Yan; Chuan-Gang Han (Metabolic Brain Disease, 2022)

Geochronology and geochemistry of monzonitic granites from the eastern central Qilian Block, northwest China - Dongyi Lv; Erfeng Ren; Jilong Han; Binkai Li; Sha Yang (Journal of Earth System Science, 2022)

A Shuttling Protein Kank1 Plays Important Role in the Sex Determination in Yellow Drum - Sha Sun; Jieping Liu; Sen Zhang; Qiwei He; Wei Han; Kun Ye; Fang Han; Wanbo Li; Zhiyong Wang (Frontiers in Marine Science, 2022)
Sex is one of the most important scientific topics, and the existence of sex dimorphism is a conserved feature in vertebrate taxa. The research on sex-determining genes and sex chromosome evolution is a hot topic in biology. The majority of sex-determining genes expressed in somatic cells, and reciprocal interactions between germ cells and somatic cells, are important for gonadal differentiation. However, the knowledge of how signals are transmitted between somatic cells and germ cells remains unclear. In this study, we confirmed the 36 dph was a sex determination critical stage in yellow drum through transcriptome analysis at the early development stages. We further found that Kank1 participated in the germ cells’ motility process in yellow drum through KEGG pathway analysis together with protein-protein interaction network. With the dual-luciferase reporter assay, we detected that Kank1 increased the transcription of dmrt1_Luc gene in CHO cells and 293T cells. Additionally, we observed that Kank1 was not only expressed in the cytoplasm but also in the nucleus in CHO cells through a fluorescence microscope. These results suggest that Kank1 acts as a shuttling protein as in humans and may play a difunctional role at the early gonad development stage in yellow drum, and it not only participated in the germ cells’ motility but also increased the expression of dmrt1 in yellow drum.

Microbial traits determine soil C emission in response to fresh carbon inputs in forests across biomes - Chengjie Ren; Jieying Wang; Felipe Bastida; Manuel Delgado‐Baquerizo; Yuanhe Yang; Jun Wang; Zekun Zhong; Zhenghu Zhou; Shuohong Zhang; Yaoxin Guo; Sha Zhou; Gehong Wei; et al. (Global Change Biology, 2022)
Soil priming is a microbial‐driven process, which determines key soil–climate feedbacks in response to fresh carbon inputs. Despite its importance, the microbial traits behind this process are largely undetermined. Knowledge of the role of these traits is integral to advance our understanding of how soil microbes regulate carbon (C) emissions in forests, which support the largest soil carbon stocks globally. Using metagenomic sequencing and 13 C‐glucose, we provide unprecedented evidence that microbial traits explain a unique portion of the variation in soil priming across forest biomes from tropical to cold temperature regions. We show that microbial functional profiles associated with the degradation of labile C, especially rapid simple sugar metabolism, drive soil priming in different forests. Genes involved in the degradation of lignin and aromatic compounds were negatively associated with priming effects in temperate forests, whereas the highest level of soil priming was associated with β‐glucosidase genes in tropical/subtropical forests. Moreover, we reconstructed, for the first time, 42 whole bacterial genomes associated with the soil priming effect and found that these organisms support important gene machinery involved in priming effect. Collectively, our work demonstrates the importance of microbial traits to explain soil priming across forest biomes and suggests that rapid carbon metabolism is responsible for priming effects in forests. This knowledge is important because it advances our understanding on the microbial mechanisms mediating soil–climate feedbacks at a continental scale.

Design and Characterization of HY-038 Solid Dispersions via Spray Drying Technology: In Vitro and In Vivo Evaluations - Taotao Jiang; Limei Han; Enhao Lu; Wenxiu He; Shilin Du; Xianyi Sha (AAPS PharmSciTech, 2021)

Therapeutic Potential of Cytokines in Demyelinating Lesions After Stroke - Yi-Sha Guo; Mei Yuan; Yu Han; Xin-Ya Shen; Zhen-Kun Gao; Xia Bi (Journal of Molecular Neuroscience, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Serum Iron and Ferritin Levels Are Correlated with Complement C3 - Shuang Wen; Yeqin Sha; Yinling Li; Zhilian Rui; Chenhong Si; Yuning Zhou; Fengfeng Yan; Bicheng Wang; Jingming Hu; Xu Han; Dongyan Shi (Biological Trace Element Research, 2021)

An Assessment of Marine Ecosystem Damage from the Penglai 19-3 Oil Spill Accident - Haiwen Han; Shengmao Huang; Shuang Liu; Jingjing Sha; Xianqing Lv (Journal of Marine Science and Engineering, 2021)
Oil spills have immediate adverse effects on marine ecological functions. Accurate assessment of the damage caused by the oil spill is of great significance for the protection of marine ecosystems. In this study the observation data of Chaetoceros and shellfish before and after the Penglai 19-3 oil spill in the Bohai Sea were analyzed by the least-squares fitting method and radial basis function (RBF) interpolation. Besides, an oil transport model is provided which considers both the hydrodynamic mechanism and monitoring data to accurately simulate the spatial and temporal distribution of total petroleum hydrocarbons (TPH) in the Bohai Sea. It was found that the abundance of Chaetoceros and shellfish exposed to the oil spill decreased rapidly. The biomass loss of Chaetoceros and shellfish are 7.25×1014~7.28×1014 ind and 2.30×1012~2.51×1012 ind in the area with TPH over 50 mg/m3 during the observation period, respectively. This study highlights the evaluation of ecological resource loss caused by the oil spill, which is useful for the protection and restoration of the biological resources following the oil spill.

The pore characteristics and its geochemical and mineralogical controls of marine-continental transitional shales from Keluke Formation in the Qaidam Basin, Northwest China - Sha-sha Sun; Jie Dai; Hui Han; Peng Pang; Chen Guo; Zhen-gang Ding; Yuan Gao (Arabian Journal of Geosciences, 2021)

Cloning and Characterization of a Ginsenoside-Hydrolyzing α-L-Arabinofuranosidase, CaAraf51, From Cellulosimicrobium aquatile Lyp51 - Sha-Sha Zuo; Yu-Chen Wang; Ling Zhu; Jiang-Yuan Zhao; Ming-Gang Li; Xiu-Lin Han; Meng-Liang Wen (Current Microbiology, 2020)

Deubiquitylatinase inhibitor b-AP15 induces c-Myc-Noxa-mediated apoptosis in esophageal squamous cell carcinoma - Beibei Sha; Xiaoyu Chen; Han Wu; Miaomiao Li; Jianxiang Shi; Longhao Wang; Xingge Liu; Ping Chen; Tao Hu; Pei Li (Apoptosis, 2019)

Visualizing DC morphology and T cell motility to characterize DC-T cell encounters in mouse lymph nodes under mTOR inhibition - Qiaoya Lin; Zheng Liu; Meijie Luo; Hao Zheng; Sha Qiao; Chenlu Han; Deqiang Deng; Zhan Fan; Yafang Lu; Zhihong Zhang; Qingming Luo (Science China Life Sciences, 2019)

AdipoRon, an adiponectin receptor agonist, attenuates cardiac remodeling induced by pressure overload - Ning Zhang; Wen-Ying Wei; Hai-Han Liao; Zheng Yang; Can Hu; Sha-sha Wang; Wei Deng; Qi-Zhu Tang (Journal of Molecular Medicine, 2018)

Effects of different levels of sweet potato in feeds on body composition and digestive enzymes activities of Apostichopus japonicas Selenka - Bin Zhao; Wei Hu; Chenglin Li; Sha Han; Tao Xu (Journal of Oceanology and Limnology, 2018)

Diversity of Fusarium species associated with root rot of sugar beet in China - Sha Cao; Naibo Yang; Can Zhao; Jia Liu; Chenggui Han; Xuehong Wu (Journal of General Plant Pathology, 2018)

Characterization of the complete genome of euonymus yellow vein associated virus, a distinct member of the genus Potexvirus, family Alphaflexiviridae, isolated from Euonymus bungeanus Maxim in Liaoning, Northern China - Caixia Yang; Tong Han; Jingjing Fu; Yiming Liao; Sha Chen (Archives of Virology, 2018)

Effects of dietary fresh fermented soybean meal on growth performance, ammonia and particulate matter emissions, and nitrogen excretion in nursery piglets - Sai-sai Cheng; Yuan Li; Shi-jie Geng; Luan-sha Hu; Xiong-feng Fu; Xin-yan Han (Journal of Zhejiang University-SCIENCE B, 2017)

Anti-glomerular basement membrane glomerulonephritis with thrombotic microangiopathy: a case report - Xiao-juan Yu; Sha-sha Han; Su-xia Wang; Xiao-yu Jia; Wei-yi Guo; Zhao Cui; Feng Yu; Fu-de Zhou; Ming-hui Zhao (Immunologic Research, 2017)

Predicting the shift of threatened ungulates’ habitats with climate change in Altun Mountain National Nature Reserve of the Northwestern Qinghai-Tibetan Plateau - Xiaoyu Wu; Shikui Dong; Shiliang Liu; Xukun Su; Yuhui Han; Jianbin Shi; Yong Zhang; Zhenzhen Zhao; Wei Sha; Xiang Zhang; Feng Gao; Donghua Xu (Climatic Change, 2017)

Induced Pluripotent Stem Cells in Huntington’s Disease: Disease Modeling and the Potential for Cell-Based Therapy - Ling Liu; Jin-Sha Huang; Chao Han; Guo-Xin Zhang; Xiao-Yun Xu; Yan Shen; Jie Li; Hai-Yang Jiang; Zhi-Cheng Lin; Nian Xiong; Tao Wang (Molecular Neurobiology, 2016)

Adenylate kinase: a novel antigen for immunodiagnosis and subunit vaccine against tuberculosis - Yangjiong Xiao; Wei Sha; Zhaofeng Tian; Yingying Chen; Ping Ji; Qin Sun; Huiyu Wang; Shujun Wang; Yong Fang; Han-Li Wen; Hui-min Zhao; Jie Lu; et al. (Journal of Molecular Medicine, 2016)

Canonical Wnt signaling pathway contributes to the proliferation and survival in porcine pancreatic stem cells (PSCs) - Xin He; Wei Han; Shu-xian Hu; Ming-zhi Zhang; Jin-lian Hua; Sha Peng (Cell and Tissue Research, 2015)

Attenuated Blood-Brain Barrier Dysfunction by XQ-1H Following Ischemic Stroke in Hyperlipidemic Rats - Weirong Fang; Lan Sha; Nandani Darshika Kodithuwakku; Jie Wei; Rui Zhang; Dan Han; Lishun Mao; Yunman Li (Molecular Neurobiology, 2015)

Analysis of the Drought Stress-Responsive Transcriptome of Black Cottonwood (Populus trichocarpa) Using Deep RNA Sequencing - Sha Tang; Yan Dong; Dan Liang; Zhoujia Zhang; Chu-Yu Ye; Peng Shuai; Xiao Han; Ying Zhao; Weilun Yin; Xinli Xia (Plant Molecular Biology Reporter, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

Preparation and Characterization of Cisplatin Magnetic Solid Lipid Nanoparticles (MSLNs): Effects of Loading Procedures of Fe3O4 Nanoparticles - Sha Zhao; Yongle Zhang; Yazhu Han; Jing Wang; Jie Yang (Pharmaceutical Research, 2015)

Numerical study of sediment transport on a tidal flat with a patch of vegetation - Gangfeng Ma; Yun Han; Arash Niroomandi; Sha Lou; Shuguang Liu (Ocean Dynamics, 2015)

Erratum to: Poplar GATA transcription factor PdGNC is capable of regulating chloroplast ultrastructure, photosynthesis, and vegetative growth in Arabidopsis under varying nitrogen levels - Yi An; Xiao Han; Sha Tang; Xinli Xia; Weilun Yin (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Poplar GATA transcription factor PdGNC is capable of regulating chloroplast ultrastructure, photosynthesis, and vegetative growth in Arabidopsis under varying nitrogen levels - Yi An; Xiao Han; Sha Tang; Xinli Xia; Weilun Yin (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Bioaccumulation, subcellular, and molecular localization and damage to physiology and ultrastructure in Nymphoides peltata (Gmel.) O. Kuntze exposed to yttrium - Yongyang Fu; Feifei Li; Ting Xu; Sanjuan Cai; Weiyue Chu; Han Qiu; Sha Sha; Guangyu Cheng; Qinsong Xu (Environmental Science and Pollution Research, 2014)

Populus euphratica: the transcriptomic response to drought stress - Sha Tang; Haiying Liang; Donghui Yan; Ying Zhao; Xiao Han; John E. Carlson; Xinli Xia; Weilun Yin (Plant Molecular Biology, 2013)

Copper ultrastructural localization, subcellular distribution, and phytotoxicity in Hydrilla verticillata (L.f.) Royle - Qinsong Xu; Han Qiu; Weiyue Chu; Yongyang Fu; Sanjuan Cai; Haili Min; Sha Sha (Environmental Science and Pollution Research, 2013)

(−)-Epigallocatechin-3-gallate alleviates spatial memory impairment in APP/PS1 mice by restoring IRS-1 signaling defects in the hippocampus - Ning Jia; Kun Han; Jing-Jing Kong; Xiu-Mei Zhang; Sha Sha; Gui-Ru Ren; Yun-Peng Cao (Molecular and Cellular Biochemistry, 2013)

Variations in leaf morphology and DNA methylation following in vitro culture of Malus xiaojinensis - Huang Huang; Sha Sha Han; Yi Wang; Xin Zhong Zhang; Zhen Hai Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Large-scale sequencing of normalized full-length cDNA library of soybean seed at different developmental stages and analysis of the gene expression profiles based on ESTs - Ai-Hua Sha; Chen Li; Xiao-Hong Yan; Zhi-Hui Shan; Xin-An Zhou; Mu-Lan Jiang; Han Mao; Bo Chen; Xia Wan; Wen-Hui Wei (Molecular Biology Reports, 2012)

Nitrogen fixation of epiphytic plants enwrapping trees in Ailao Mountain cloud forests, Yunnan, China - Bin Han; Xiaoming Zou; Jijun Kong; Liqing Sha; Hede Gong; Zhen Yu; Tong Cao (Protoplasma, 2010)

Molecular cloning, tissue distribution and bioinformatics analyses of the rabbit BK channel β1 subunit gene - Xiao-Yong Zhang; Sha Wang; Zhen Yan; Yi Wan; Wei Wang; Guang-Bin Cui; Pang Du; Ke-Jun Ma; Wei Han; Ying-Qi Zhang; Jing-Guo Wei (Molecular Biology Reports, 2008)

Molecular Cloning and Expression Analysis of the Myostatin Gene in Sea Perch (Lateolabrax japonicus) - Han-Qing Ye; Song-Lin Chen; Zhen-Xia Sha; Yang Liu (Marine Biotechnology, 2007)

Pluripotency and Chimera Competence of an Embryonic Stem Cell Line from the Sea Perch (Lateolabrax japonicus) - Song-Lin Chen; Zhen-Xia Sha; Han-Qing Ye; Yang Liu; Yong-Sheng Tian; Yunhan Hong; Qi-Sheng Tang (Marine Biotechnology, 2007)